Sensitization of Non-Small Cell Lung Cancer Cells to Gefitinib and Reversal of Epithelial–Mesenchymal Transition by Aloe-Emodin Via PI3K/Akt/TWIS1 Signal Blockage - Peng, Minghui; Zheng, Zhuifeng; Chen, Shaoyang; Fang, Le; Feng, Rongxiu; Zhang, Lijun; Tang, Qingnan; Liu, Xuewen (Frontiers in Oncology, 2022)
Objective To explore the impacts of AE (aloe-emodin) in gefitinib-resistant NSCLC (non-small cell lung cancer) cells and the corresponding mechanism. Methods PC9 and PC9-GR cells were cultured and treated by gefitinib, AE, or the combination of the two drugs. Then, viability, apoptosis, migration and invasion of cells were investigated using CCK-8, TUNEL, wound healing assay, and transwell assay, respectively. Female BALB/c nude mice were employed for the establishment of xenograft tumor models to examine the role of AE in tumor growth. Results PC9-GR cells showed reduced apoptosis and enhanced cell viability, migration and invasion upon treatment by gefitinib, compared with PC9 cells. E-cahherin in PC9-GR cells was down-regulated, while Vimentin, Snail2 (or Slug) and Twist1 in PC9-GR cells were up-regulated, compared with PC9 cells. Meanwhile, treatment by a combination of gefitinib and AE significantly strengthened apoptosis of PC9-GR cells, while attenuated their migration and invasion, compared with the control group or treatment by gefitinib or AE alone. WB results showed that AE could reverse EMT and activation of PI3K/AKT signalling pathway in PC9-GR cells. In vivo experiments showed that tumor growth and EMT of PC9-GR cells were dramatically repressed after treatment by a combination of AE and gefitinib. Additionally, the use of SC97 (a PI3K/Akt pathway activator) could counteract the effects of AE in gefitinib-resistant PC9 cells. Conclusions AE could enhance the gefitinib sensitivity of PC9-GR cells and reverse EMT by blocking PI3K/Akt/TWIS1 signal pathway.